2007
DOI: 10.1017/s0003581500000895
|View full text |Cite
|
Sign up to set email alerts
|

Edward The Confessor's Chapel, Westminster Abbey: The Origins of the Royal Mausoleum and its Cosmatesque Pavement

Abstract: It has hitherto been argued that Edward the Confessor's Chapel at Westminster Abbey, built by Henry III in 1246–59, was established as the royal mausoleum only from the 1290s. In 2005 a ground penetrating radar survey of the chapel floor revealed many anomalies, some of which can be interpreted as grave cists. A re-examination of the written and physical evidence for subfloor burials in the chapel suggests that, among other early burials, at least five of Edward I's children were interred here in the period 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…This is not a surprising result, however, given that the Shrine Chapel has been a sacred burial area reserved for royal personages, their close relatives and advisors since the Abbey was constructed. In addition, some months after the GPR surveys were carried out, historical research revealed information indicating that these are likely to be graves of royal children, most probably those of Henry III’s son, Edward I (Badham 2007). Although there are reliable historical records indicating the burial of a number of courtiers and royal relations, including children, no visible mark or memory remained to suggest the location of these graves prior to the GPR survey.…”
Section: Survey Processing and Results From The 2005 Low‐frequency Sumentioning
confidence: 99%
See 1 more Smart Citation
“…This is not a surprising result, however, given that the Shrine Chapel has been a sacred burial area reserved for royal personages, their close relatives and advisors since the Abbey was constructed. In addition, some months after the GPR surveys were carried out, historical research revealed information indicating that these are likely to be graves of royal children, most probably those of Henry III’s son, Edward I (Badham 2007). Although there are reliable historical records indicating the burial of a number of courtiers and royal relations, including children, no visible mark or memory remained to suggest the location of these graves prior to the GPR survey.…”
Section: Survey Processing and Results From The 2005 Low‐frequency Sumentioning
confidence: 99%
“…This chapel lies behind (i.e., to the east of) the present High Altar, separated from it by a 15 th century stone screen. On his death in 1272, Henry III is thought to have been buried within the same large vault formerly used by his ancestor until such time as a suitable royal tomb had been constructed for him (Badham 2007). This same tomb was re‐used once more in 1290 when Queen Eleanor of Castile, the wife of Henry III’s son and successor, died suddenly.…”
Section: Background To the Investigationmentioning
confidence: 99%
“…7]. These are likely to be graves of royal children, most probably those of Edward 1 [3]. Although there are historical records indicating the burial of a number of courtiers and royal relations, including children, no visible mark or memory remained to suggest the location of these graves prior to the GPR survey.…”
Section: Survey Resultsmentioning
confidence: 99%
“…This can be seen also in Figures 4,5 & 7. It is therefore likely that the burials identified by both the 400MHz and 4GHz surveys are being detected because of their associated voids. Subsequent to the survey, it has been possible to put names to some of these burials and suggestions for the identities of others although the original occupants may have been removed [3].…”
Section: Discussion Of the Survey Resultsmentioning
confidence: 99%
See 1 more Smart Citation